A review of literature on the potentials and problems of face-to-face and online peer feedback and the patterns of interaction among ESL/EFL learners in a peer feedback environment - Muhammad Danial Baharudin,; Abu Bakar Razali, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Peer feedback is one of the many elements that contribute to the mastery of the English language writing skills. However, ESL/EFL learners often faced difficulties in giving and receiving peer feedback as they often are not able to give or understand feedback from their peers. In uncovering the potentials and problems with peer feedback amongst ESL/EFL learners in developing their writing performance, this review provides a description on the nature and elements in face-to-face and online peer feedback, and report a review of literature on the patterns of interaction showcased by ESL/EFL students during the peer feedback sessions. Subsequently, the research gaps are identified and recommendations for future research are highlighted. The authors found that although some problems occurred when the peer feedback sessions are implemented, such as the preferences for teacher feedback and negative patterns of interaction, generally it is effective in improving ESL/EFL students’ writing performance as both face-to-face and online peer feedback provides multiple benefits in their writing process (e.g., provides opportunities to discuss critical elements in writing, benefit from sense of anonymity in online platform and seize the opportunity for collaborative learning). However, the authors discovered that studies on the patterns of interaction are limited especially in an online peer feedback environment among ESL learners. Thus, this review recommends for future research to close this gap to uncover the potentials of the peer feedback (especially online peer feedback) in developing ESL learners’ writing performance. As a whole, this review of literature brings great significance because it provides inputs to teachers on the strengths and weaknesses of the peer feedback approach (both face-to-face and online) and the best patterns of interaction developing the students’ writing performance. These inputs can also benefit educational institutions and curriculum developers in introducing effective learning activities or tasks that involve the face-to-face and online peer feedback approach in the curriculum.